2006
DOI: 10.3892/or.16.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Clinical added-value of 18FDG PET in neuroendocrine-merkel cell carcinoma

Abstract: Abstract. Merkel cell carcinoma (MCC) is a rare and highly malignant skin cancer with neuroendocrine differentiation. We studied the potential value of 18 FDG PET in the management of MCC. Eleven patients with MCC were examined by 18 FDG PET and PET-CT for staging purpose (n=4) or for detection of recurrence (n=7). Qualitative and quantitative interpretation of PET studies was performed routinely. 18 FDG PET observations were compared to clinical and radiological findings. In 6 patients, PET findings were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 21 publications
1
44
0
1
Order By: Relevance
“…3,11,12 More recently, fluorine-18-fluorodeoxyglucose (F-18-FDG)ePET and F-18-FDGePET/CT have shown promise in detecting nodal disease and metastasis and in affecting the staging and management of MCC. 4,5,9,10,[13][14][15][16] Little information exists comparing the sensitivity of these imaging methods with each other and with the gold standard of histopathologic nodal evaluation. We sought to document sensitivity and specificity of various imaging modalities, including CT, MRI, F-18-FDGePET, and F-18-FDGePET/CT, with regard to the primary staging of MCC through histopathologic nodal evaluation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,11,12 More recently, fluorine-18-fluorodeoxyglucose (F-18-FDG)ePET and F-18-FDGePET/CT have shown promise in detecting nodal disease and metastasis and in affecting the staging and management of MCC. 4,5,9,10,[13][14][15][16] Little information exists comparing the sensitivity of these imaging methods with each other and with the gold standard of histopathologic nodal evaluation. We sought to document sensitivity and specificity of various imaging modalities, including CT, MRI, F-18-FDGePET, and F-18-FDGePET/CT, with regard to the primary staging of MCC through histopathologic nodal evaluation.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] For imaging in primary staging of MCC, the traditional recommendations have included CT, octreotide scans, ultrasonography, and MRI. 3,11,12 More recently, fluorine-18-fluorodeoxyglucose (F-18-FDG)ePET and F-18-FDGePET/CT have shown promise in detecting nodal disease and metastasis and in affecting the staging and management of MCC.…”
mentioning
confidence: 99%
“…Lin et al (23) reported the increased sensitivity of 18 F-FDG PET for detecting MCC recurrence compared with CT. Furthermore, in a study by Belhocine et al (24), 18 F-FDG PET/CT was compared with CT, MRI and bone scan alone in 11 patients. A sensitivity of 92% …”
Section: Discussionmentioning
confidence: 99%
“…Les premiers résultats ont fait état d'une sensibilité égale ou supérieure de cette technique par rapport à la tomodensitométrie, mais les études ulté-rieures ont montré un intérêt relatif du fait de la présence de faux positifs et de faux négatifs [28]. La tomographie par émission de positrons au fluorodéoxyglucose a certainement un intérêt en termes de sensibilité de dépistage des métastases, notamment ganglionnaires, par rapport à la tomodensitométrie, mais les résultats demandent à être validés par des études à plus grande échelle [29,30].…”
Section: Bilan D'extension Initialunclassified